Perfidia [compact disc, unabridged] - Ellroy, James, 1948- (Random House Audio : Books on Tape, 2014)
The Japanese have bombed Pearl Harbor. The United States teeters on the edge of war. The roundup of allegedly treasonous Japanese Americans is about to begin. And in L.A., a Japanese family is found dead. Murder or ritual suicide?